Infusing sub-Saharan culinary heritage in university learning for a delectable academic journey - Sasi Gangiah (Inkanyiso)
African culture and tradition, deeply rooted in our community, encompass a rich tapestry of values, rituals, festivals, and literary treasures. Among the vibrant facets of this cultural heritage is African cuisine. Indigenous dishes exhibit delicate flavours, while others manifest a symphonic richness forged from basic ingredients with skilled artistry. The diversity in African cuisines is remarkable, with each country boasting distinctive culinary traditions. Unfortunately, the spectre of colonisation has led to Eurocentric dominance in culinary education. A decolonised approach in catering management education is needed to celebrate our culture and tradition, emphasising the commonalities and differences in African cuisines. This complex endeavour involves implementing decolonisation while incorporating indigenous African ingredients. Harnessing African knowledge is pivotal in revitalising regional culinary traditions and inspiring potential entrepreneurial ventures. This qualitative study explores the role of African food festivals in driving the decolonisation of culinary education in the departments offering food service-related courses. In addition, a comprehensive literature analysis on African cuisines using a structured search methodology sheds light on the subject.